Development of severe colitis is associated with lung inflammation and pathology - Raftery, April L.; O’Brien, Caitlin A.; Harris, Nicola L.; Tsantikos, Evelyn; Hibbs, Margaret L. (Frontiers in Immunology, 2023)
Inflammatory bowel diseases (IBD) such as Crohn’s disease and ulcerative colitis are chronic relapsing diseases that affect the gastrointestinal tract, most commonly the colon. A link between the gut and the lung is suggested since patients with IBD have an increased susceptibility for chronic inflammatory lung disease. Furthermore, in the absence of overt lung disease, IBD patients have worsened lung function and more leukocytes in sputum than healthy individuals, highlighting a conduit between the gut and lung in disease. To study the gut-lung axis in the context of IBD, we used TCRδ-/- mice, which are highly susceptible to dextran sulfate sodium (DSS) due to the importance of γδ T cells in maintenance of barrier integrity. After induction of experimental colitis using DSS, the lungs of TCRδ-/- mice exhibited signs of inflammation and mild emphysema, which was not observed in DSS-treated C57BL/6 mice. Damage to the lung tissue was accompanied by a large expansion of neutrophils in the lung parenchyma and an increase in alveolar macrophages in the lung wash. Gene expression analyses showed a significant increase in Csf3, Cxcl2, Tnfa, and Il17a in lung tissue in keeping with neutrophil infiltration. Expression of genes encoding reactive oxygen species enzymes and elastolytic enzymes were enhanced in the lungs of both C57BL/6 and TCRδ-/- mice with colitis. Similarly, surfactant gene expression was also enhanced, which may represent a protective mechanism. These data demonstrate that severe colitis in a susceptible genetic background is sufficient to induce lung inflammation and tissue damage, providing the research community with an important tool for the development of novel therapeutics aimed at reducing co-morbidities in IBD patients.